2016
DOI: 10.1038/srep19727
|View full text |Cite
|
Sign up to set email alerts
|

Generating trunk neural crest from human pluripotent stem cells

Abstract: Neural crest cells (NCC) are stem cells that generate different lineages, including neuroendocrine, melanocytic, cartilage, and bone. The differentiation potential of NCC varies according to the level from which cells emerge along the neural tube. For example, only anterior “cranial” NCC form craniofacial bone, whereas solely posterior “trunk” NCC contribute to sympathoadrenal cells. Importantly, the isolation of human fetal NCC carries ethical and scientific challenges, as NCC induction typically occur before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 55 publications
5
72
0
Order By: Relevance
“…This observation indicates that TH-MYCN neuroblastoma sphere-forming cells underwent spontaneous differentiation in culture. We further investigated the responsiveness of these sphere-forming cells to retinoic acid (RA), a differentiation inducer of neuroblastoma cells (Sidell, 1982) and neural crest cells (Dupin and Le Douarin, 1995; Huang et al, 2016). Treatment of mouse neuroblastoma spheres with RA induced growth arrest as evidenced by the marked reduction in sphere size and numbers, as well as the total number of sphere cells (Figures 2A-2C).…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates that TH-MYCN neuroblastoma sphere-forming cells underwent spontaneous differentiation in culture. We further investigated the responsiveness of these sphere-forming cells to retinoic acid (RA), a differentiation inducer of neuroblastoma cells (Sidell, 1982) and neural crest cells (Dupin and Le Douarin, 1995; Huang et al, 2016). Treatment of mouse neuroblastoma spheres with RA induced growth arrest as evidenced by the marked reduction in sphere size and numbers, as well as the total number of sphere cells (Figures 2A-2C).…”
Section: Resultsmentioning
confidence: 99%
“…Human NC formation models have reported mixed and even contradictory information regarding the contribution of BMP signaling. Some groups require BMP inhibition (Chambers et al, 2012; Mica et al, 2013), but others found BMP inhibition dispensable for NC formation from hPSCs (Fukuta et al, 2014; Huang et al, 2016; Menendez et al, 2011). By contrast, our model of anterior NC formation requires BMP signaling (Leung et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Retinoic Acid (RA) signaling has been linked with posteriorization of embryonic tissues and neural crest (Fattahi et al, 2016; Fukuta et al, 2014; Huang et al, 2016; Mica et al, 2013); specifically, addition of RA promotes the expression of vagal identity HOX genes in NC cultures. It has been proposed that RA and FGF exert antagonistic effects to modulate the anterior-posterior character of the neural tube and NCCs (Cunningham et al, 2015; Diez del Corral et al, 2003; Olivera-Martinez and Storey, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural crest (NC) related deficiencies are the cause of multiple human diseases and the term "neurocristopathies" has been proposed to denote syndromes or tumors involving NCCs. Neural crest derived malignancies include cancers such as melanoma, neuroblastoma and neurofibromatosis (Vega-Lopez et al, 2018) and the use of hPSCs-derived NCCs for modeling human NC diseases is an attractive in vitro experimental approach (Fattahi et al, 2016, Huang et al, 2016. We showed that hPSCs-derived NCC, when injected into the gastrulating mouse embryo, migrated along the dorso-lateral migration route contributing to the pigment system of the mouse, suggesting that this platform may be used to model neurocristopathies in vivo (Cohen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%